Effects Of Credit Attitude And Social Economic Factors On The Usage Of Credit Facilities Among Young Adults In Malaysia - Krishnanandan, Menaka (2011)
This study aims to explore if economic, social and attitude factors have an effect on the usage of credit facilities among the young adults in Malaysia.